The Fund's Medium-Term Income : Outlook and Options. (Policy Papers; Policy Paper ;, 2006)
This paper puts forward a number of measures which, if implemented, would eliminate the income gap in FY07. However, these measure still leave a large financing gap moving forward. Therefore, further work is needed to examine mechanisms for financing the Fund's operations in the medium-term in a manner that ensures that the Fund has a sound financial basis to operate without relying on sharp growth in lending.